Development of interactive software (Shear stress in beams) - Wang, Fei (2016)
The main objective of this project is to present the distributed shear stresses in beams in an interactive software, using the computer programming. This computer program has been written in JavaScript, includes an user-friendly graphic interface, and it can be accessed freely on http://wang1015.1apps.com/Shear%20Stress/HomePage.html. The developed program can determine the unknown reactions on either statically determinate or indeterminate beams, to compute the shear force the shear stresses at any location along a given beam. Moreover, the developed codes allow performing shear force and stress analysis for various type of beam under different combination of loads includes non-linear distributed load. This computer program has also been designed and developed with the aid of algorithm and flowchart shown in the report. Four main sections of the program are menus and tables for data input, intermediate calculations, graphical output and numerical results. Students receive interactive graphical feedback for better learning experiences while they are working on solving the problems. Worked examples from textbooks have also been utilized to get the results for comparison and validation. Although this program is restricted to beam with constant cross-section, future development can equip ability to address more complicated shapes and cases of beams. The program is expected to be a useful educational tool in helping students to learn effectively during the course Mechanics of Materials.